Continuous Flow Ventilatory Support: Physical, Mathematical, and Clinical Prerequisites and Principles - Pavol Török; Peter Сandík; Jan Salantay; Milan Majek; Jan Kolnik (Общая реаниматология, 2006)
The authors describe the theoretical bases of a new ventilatory support procedure that is called by the authors as continuous flow ventilatory support (CFVS). In the theoretical part they provide evidence for this procedure of ventilatory support and explain the basic mathematical and physiological principles of the described procedure and artificial ventilation and compare the possibilities of using CFVS with a multi-jet insufflation catheter (VIK®) versus a terminal orifice one (JTO). Physical and mathematical analyses on a model of the artificial lung in the static and dynamic modes revealed that there was a difference in the values of the maximum inspiratory pressure and positive end-expiratory pressure (PEEP), which was greater with the terminal orifice catheter. There was evidence that the use of CFVS with a multi-jet insufflation catheter or a terminal one-orifice one presented a risk of barotrauma and made the value of dynamic PEEP with a gas flow of as high as 20—26 l/min minimal when CFVS. The latter with a multi-jet insufflation catheter is most suitable when higher gas flows Qin above 25—28 l/min are applied. In conclusion, the authors consider that CFVS with a multi-jet insufflation catheter is technically more effective and substantially higher gas flows may be used as in the application of a terminal one-orifice catheter without a risk of elevated airway pressure and without increased ventilation performance on expiration.